Poor Efficacy and Tolerability of Stavudine, Didanosine, and Efavirenz-based Regimen in Treatment-Naive Patients in Senegal - Canestri, Anna (Medscape, 2007)
OBJECTIVE: To study the effectiveness and tolerance of an antiretroviral therapy (ART) regimen composed of the antiretroviral agents (ARVs) stavudine (d4T) plus didanosine (ddI) plus efavirenz (EFV) in patients with advanced HIV infection in Senegal. DESIGN AND METHODS: This was an open-label, single-arm, 18-month trial in treatment-naive patients. The primary virologic end point was the percentage of patients with plasma HIV RNA < 500 copies/mL at months 6 (M6), 12 (M12) and 18 (M18). The primary analysis was done as intent-to-treat. RESULTS: The staging of HIV disease, performed using the definitions of the US Centers for Disease Control and Prevention (CDC), was CDC stage B or C for all 40 recruited patients. At baseline, the mean CD4+ cell count was 133 ± 92/mcL (± standard deviation [SD]; range 1–346), and 23% of patients had CD4+ cell counts below 50/mcL. The mean baseline plasma HIV RNA level was 5.5 ± 0.4 log(10) copies/mL (± SD; range 4.6–5.9). The proportion of patients with plasma HIV-1 RNA below 500 copies/mL fell during the study from 73% (95% CI [56; 85]) at M6 to 56% (95% CI [41; 73]) at M12 and 43% (95% CI [27; 59]) at M18. Plasma HIV-RNA was below 50 copies/mL in 50% of study subjects (95% CI [31; 66]) at M6, 43% (95% CI [27; 59]) at M12, and 33% (95% CI [19; 49]) at M18. The mean increase in the CD4+ cell count was 105 ± 125/mcL (n = 38) at M3 and 186 ± 122/mcL (n = 21) at M18. Eight patients died, including 6 because of infectious complications. The last viral load (VL) value before death was < 500 copies/mL in all these patients except 1 nonadherent patient. Fifteen patients (37.5%) had peripheral neuropathy that was severe enough in 5 patients (12.5%) to require ddI and d4T discontinuation. CONCLUSION: Virologic efficacy combination therapy with d4T, ddI, and EFV was measured by the percentage of patients with plasma HIV RNA values below 500 copies/mL and 50 copies/mL; for both parameters, virologic efficacy decreased during the study period. This is explained by the high mortality rate (20%) and treatment modifications due to adverse events (13%). These data strengthen the recently revised World Health Organization (WHO) guidelines advocating initiation of highly active antiretroviral therapy (HAART) before profound CD4 lymphocyte depletion occurs and avoiding HAART regimens containing d4T and ddI because of treatment-limiting side effects.